A revision of the New Zealand weevil genus Irenimus Pascoe, 1876 (Coleoptera: Curculionidae: Entiminae) - Brown, Samuel D. J. (Zootaxa, 2017)
The taxonomy of the New Zealand weevil genus Irenimus Pascoe, 1876 is revised, resulting in a narrower concept of the genus than has been considered in recent decades. In total, the genus now contains only seven species. In addition to the type species, I. parilis Pascoe, 1876, the genus contains I. duplex (Broun, 1904) and five newly described species: I. aniptus new species (type locality, Oamaru, DN), I. crinitus new species (type locality, Hakataramea Valley, SC), I. minimus new species (type locality, Alexandra, CO), I. stichus new species (type locality, Tekapo, MK) and I. thoracicus new species (type locality, Oamaru, DN). The genus Chalepistes new genus is established to contain the majority of species previously described in the genus Catoptes Schönherr, 1842, but also including species described in Brachyolus White, 1846; Irenimus Pascoe, 1876; Inophloeus Pascoe, 1875; and Nicaeana Pascoe, 1877. A total of 27 valid described species are new combinations with Chalepistes: C. aequalis (Broun, 1895) (from Irenimus), C. albosparsus (Broun, 1917) (from Irenimus), C. apicalis (Broun, 1923) (from Catoptes), C. asperatus (Broun, 1914) (from Brachyolus), C. compressus (Broun, 1880) (from Irenimus), C. costifer (Broun, 1886) (from Inophloeus), C. curvus (Barratt & Kuschel, 1996) (from Irenimus), C. dehiscens (Broun, 1917) (from Catoptes), C. dugdalei (Barratt & Kuschel, 1996) (from Irenimus), C. egens (Broun, 1904) (from Irenimus), C. inaequalis (Sharp, 1886) (from Brachyolus), C. instabilis (Marshall, 1931) (from Catoptes), C. latipennis (Broun, 1893) (from Catoptes), C. limbatus (Broun, 1909) (from Catoptes), C. lobatus (Broun, 1921) (from Catoptes), C. patricki (Barratt & Kuschel, 1996) (from Irenimus), C. pensus (Broun, 1914) (from Inophloeus), C. placidus (Broun, 1914) (from Nicaeana), C. posticalis (Broun, 1893) (from Irenimus), C. rhesus (Pascoe, 1875) (from Inophloeus), C. rubidus (Broun, 1881) (from Inophloeus), C. similis (Barratt & Kuschel, 1996) (from Irenimus), C. spectabilis (Broun, 1914) (from Catoptes), C. spermophilus (Broun, 1895), revised status (from Irenimus), C. stolidus (Broun, 1886) (from Irenimus), C. tenebricus (Broun, 1893) (from Catoptes), C. vastator (Broun, 1893) (from Irenimus). Numerous new synonyms with species of Chalepistes are also proposed: Brachyolus fuscipictus Broun, 1914 and Brachyolus terricola Broun, 1917 are junior subjective synonyms of Chalepistes asperatus (Broun); Brachyolus cervalis Broun, 1903 and Brachyolus sylvaticus Broun, 1910 are junior subjective synonyms of Chalepistes costifer (Broun); Inophloeus tricostatus Broun, 1915 is a junior subjective synonym of Chalepistes pensus (Broun); Catoptes pallidipes Broun, 1917, Catoptes flaviventris Broun, 1917 and Catoptes nigricans Broun, 1917 are junior subjective synonyms of Chalepistes placidus (Broun); Inophloeus longicornis Broun, 1904, Inophloeus medius Broun, 1893, Inophloeus sulcicollis Broun, 1914 and Inophloeus suturalis Broun, 1893 are junior subjective synonyms of Chalepistes rhesus (Pascoe); Inophloeus albonotata Broun, 1893, Catoptes asperellus Broun, 1893, Irenimus bicostatus Broun, 1886, Catoptes caliginosus Broun, 1893, Catoptes chalmeri Broun, 1893, Catoptes decorus Broun, 1893, Inophloeus discrepans Broun, 1904, Catoptes fumosus Broun, 1914, Catoptes furvus Broun, 1893, Catoptes humeralis Broun, 1893, Catoptes longulus Sharp, 1886, Inophloeus nigellus Broun, 1881, Irenimus pilosellus Broun, 1886 and Catoptes scutellaris Sharp, 1886 are junior subjective synonyms of Chalepistes rubidus (Broun); Catoptes subnitidus Broun, 1914 and Catoptes curvatus Broun, 1914 are junior subjective synonyms of Chalepistes spermophilus (Broun); Catoptes brevicornis Sharp, 1886 and Catoptes vexator Broun, 1904 are junior subjective synonyms of Chalepistes stolidus (Broun); and Catoptes aemulator Broun, 1893 and Catoptes argentalis Broun, 1914 are junior subjective synonyms of Chalepistes tenebricus (Broun). Additional new combinations include Inophloeus robustus (Broun, 1917) (from Catoptes) and Nicaeana fraudator (Marshall, 1931) (from Catoptes), while Catoptes postrectus Marshall, 1931 is a new synonym of Protolobus obscurus Sharp, 1886.